The role of nitrogen-doping and the effect of the pH on the oxygen reduction reaction on highly active nitrided carbon sphere catalysts. (10th March 2019) - Eckardt, M.; Sakaushi, K.; Lyalin, A.; Wassner, M.; Hüsing, N.; Taketsugu, T.; Behm, R.J.
Abstract: Aiming at a better understanding of the molecular scale mechanism of the oxygen reduction reaction (ORR) on metal-free catalysts, we have systematically investigated this reaction in a combined experimental and theoretical approach on a set of catalysts consisting of nitrided carbon spheres. These catalysts, which were prepared similarly, but applying different carbonization/nitriding temperatures, were studied in acidic and alkaline electrolyte. The physical properties characterization of both, the bulk materials and the surface, was performed by transmission electron microscopy (TEM), N2 sorption, X-ray photoelectron spectroscopy (XPS), CHN analysis and energy dispersive X-ray spectroscopy (EDX) and Temperature Programmed Desorption (TPD) of CO2 . Electrochemical and –catalytic properties were characterized by rotating ring disk electrode (RRDE) measurements. Mechanistic aspects were explored by kinetic analysis of the ORR and by evaluation of the kinetic isotope effect (H-D exchange), using deuterated electrolytes (KOD and D2 SO4 ). In combination with density functional theory based calculations, these kinetic data provide detailed insights into the reaction mechanism and its dependence on pH effects. In acidic electrolyte, the first proton coupled electron transfer (PCET) is identified as rate determining step (RDS), while in alkaline electrolyte the first electron transfer (ET) to O2 ∗− ad is rate determining, followed by fast protonation. The potential of these highly active catalysts and the influence of structural effects are discussed. Graphical abstract: Image 1